PERAN LEMBAGA PELESTARIAN SATWA BORNEO ORANGUTAN SURVIVAL SAMBOJA LESTARI TERKAIT PERLINDUNGAN HUKUM TERHADAP SATWA YANG DILINDUNGI DARI PERDAGANGAN LIAR DI KALIMANTAN TIMUR - Akfan Kun Haq (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACTIndonesia is a very rich country with a diversity of animals, but Indonesia is also known as a country that has a long list of endangered wildlife. The main factor that threatens the extinction of these wildlife is the narrower or damaged habitat and hunting for trade. Various species of protected and endangered animals are still traded freely in Indonesia. The regulation on trade of protected animals in Indonesia has been formulated in Law No. 5 of 1990 on the Conservation of Biological Resources and Ecosystems. The existence of a restricting regulation on the trade in protected animals becomes the basis for law enforcement on the execution of its duty in handling the case of illegal trade. However, law enforcers can not work alone, because afterwards law enforcers need help from the Conservation Institute to care for the confiscated animals of the Government in the case of illegal trade. In East Kalimantan, one of the Conservation Institutions which is the Government's goal as an institution in charge of rehabilitating animals from wild trade operations is the Borneo Orangutan Survival Foundation Samboja Lestari.From the results of the study can be described that the protection of wildlife from illegal trade based on Law No. 5 of 1990 on the Conservation of Biological Resources and Ecosystems has been declared that the trade in protected animals is a criminal act. In an effort to protect the law against wildlife from the Natural Resource Conservation Center East Kalimantan has implemented the Act in performing its duties as a law enforcer in the trade of protected animals. Furthermore, East Kalimantan Natural Resource Conservation Center in cooperation with Borneo Orangutan Survival Samboja Lestari to rehabilitate animals from the illegal trade operations. Wildlife protection from wildlife in Borneo Orangutan Survival Samboja Lestari is done through three main functions through animal rescue, animal rehabilitation and conservation education as well as through the fulfillment of animal rights.